2016
DOI: 10.1038/srep22599
|View full text |Cite
|
Sign up to set email alerts
|

MiR-708 promotes steroid-induced osteonecrosis of femoral head, suppresses osteogenic differentiation by targeting SMAD3

Abstract: Steroid-induced osteonecrosis of femoral head (ONFH) is a serious complication of glucocorticoid (GC) use. We investigated the differential expression of miRs in the mesenchymal stem cells (MSCs) of patients with ONFH, and aimed to explain the relationship between GC use and the development of MSC dysfunction in ONFH. Cells were collected from bone marrow of patients with ONFH. Samples were assigned to either GCs Group or Control Group at 1:1 matched with control. We then used miRNA microarray analysis and rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 55 publications
1
74
0
1
Order By: Relevance
“…Osteonecrosis can result in debilitation and adversely affect the quality of life, frequently requiring surgical intervention. Thus far, there are no effective preventive measures for SANFH (14). Although multiple theories underlying this complication have been proposed, no pathophysiologic mechanism has been identified as the etiology for the development of osteonecrosis of the femoral head (15).…”
Section: Discussionmentioning
confidence: 99%
“…Osteonecrosis can result in debilitation and adversely affect the quality of life, frequently requiring surgical intervention. Thus far, there are no effective preventive measures for SANFH (14). Although multiple theories underlying this complication have been proposed, no pathophysiologic mechanism has been identified as the etiology for the development of osteonecrosis of the femoral head (15).…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of miR-708 also rescued the suppressive effect of glucocorticoid on osteonecrosis. 33 These data suggested that glucocorticoid might result in miR-708 overexpression to mediate its ONFH-promoting effect. This miRNA may thus act as a new therapeutic target for the prevention and treatment of ONFH.…”
Section: Mir-708mentioning
confidence: 95%
“…[45][46][47] Hao et al 33 found that the expression of miR-708 was significantly upregulated in glucocorticoid-treated and ONFH patients' mesenchymal stem cells. In addition, they found that Smad3 (small mothers against decapentaplegic 3) was a direct target of miR-708.…”
Section: Mir-708mentioning
confidence: 99%
See 2 more Smart Citations